Kinematic and dynamic analysis of passive suspension using pneumatic and flexible tire - Naderian, Kasra, 1987-; Intan Zaurah Mat Darus, supervisor; Fakulti Kejuruteraan Mekanikal (2013)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2013